The impact of ChART on the science of thymic malignancies - Detterbeck, Frank (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Thymic malignancies qualify as an orphan disease. Many hurdles stand in the way of scientific advancement for such rare diseases, including the difficulty in having an adequate and homogeneous population of patients to study, and the fact that grants and other support for research is mostly unavailable for rare diseases (1). It is clear that the only way to make progress is through grass roots efforts, collaboration, and an organizational infrastructure. This realization led to the formation of both the International Thymic Malignancy Interest Group (ITMIG) and the Chinese Alliance for Research in Thymomas (ChART).